Experiences of patients having tuberculosis (TB) regarding the use of Directly Observed Treatment Short-Course (DOTS) in the North West Province, South Africa - Maserapelo G. Serapelwane; Mashudu Davhana-Maselesele; Gaboipolelwe M. Masilo (AOSIS, 2016)
Background: Tuberculosis (TB) management remains a major challenge despite the implementation of Directly Observed Treatment Short-Course (DOTS). Some of the challenges include defaulting treatment, low TB cure rates and relapse after patients had been treated under DOTS. Objectives: This study explored and described experiences of patients having TB regarding the use of DOTS in Doctor Ruth Segomotsi Mompati District of North West Province, South Africa. The study describes and recommends support required by patients having TB who are using DOTS. Methods: A qualitative, exploratory, descriptive and contextual design was used. The population consisted of all patients having TB under DOTS who had taken treatment for 2 months and more in one of the community health centres in Doctor Ruth Segomotsi Mompati District. Purposive sampling technique was applied to select participants receiving DOTS service. In-depth unstructured individual interviews were conducted, and data saturation occurred after having interviewed 15 participants. Ethical considerations were ensured throughout the study, and data were analysed using Tesch's method of coding and analysis. Results: Two themes emerged from data and these are discussed as concerns related to ineffective use of DOTS and lack of resources as contributory factor to ineffective use of DOTS. Among other categories, poor nurse-patient relationships and difficulties in accessing the community health centre emerged as consistent themes related to default and inconsistent use of DOTS. Conclusion: Ineffective use of DOTS contributed to TB treatment default and low cure rate. Therefore, recommendations focused on strengthening effective use of DOTS for the management of TB.